DIAGNÓSTICO DE MANIFESTAÇÕES PATOLÓGICAS DE FACHADAS DE UMA RESIDÊNCIA DE DOIS PAVIMENTOS NA CIDADE DE PASSO FUNDO - RS - Santos, Mariana Mattei; Gattermann, Liliany Schramm da Silva; Novello, Marinês Silvani; Masuero, Angela Borges (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article results from a research that investigated pathologies in the external façades of a historic building with Art Déco features located in the city of Passo Fundo - RS. The structure of the work was distributed in some parts, namely: the context where the building is located, its relation to its surroundings, the specific characteristics of the building and its temporal insertion and, following the method of Lichtenstein (1986) (historical and documental study), complementary basic tests and bibliographic research. Afterwards, through the results obtained, the diagnosis of the pathological manifestations was carried out with the identification of its origins and causes and, also, the definition of the mechanisms of occurrence. With these data, it was possible to establish the prognosis and the alternatives of intervention to finally define the recommendations of conduct. As a result, it was observed that the diagnosed pathological problems may be related, in addition to the precarious and few maintenance performed, to the types of materials used, as well as anomalies resulting from the execution, lack of planning of the interventions in sequential periods as currently established maintenance manuals.